New fossil of Gaoloufangchaeta advances the origin of Errantia (Annelida) to the early Cambrian - Xiaoyu Yang; M. Teresa Aguado; Conrad Helm; Zhiqian Zhang; Christoph Bleidorn (Royal Society Open Science, 2024)
Molecular clock estimates suggest the origin of Annelida dates back to the Ediacaran period, which is in discordance with the first appearance of this taxon in the early Cambrian, as evidenced by the fossil records of stem-group and basally branching crown-group annelids. Using new material from the early Cambrian Guanshan biota (Cambrian Series 2, Stage 4), we re-interpret Gaoloufangchaeta bifurcus Zhao, Li & Selden, 2023, as the earliest known errantian annelid. Gaoloufangchaeta has a prominent anterior end bearing three pairs of putatively sensory appendages and a pair of anterior eyes; a muscular eversible pharynx with papillae is identified. The presence of enlarged parapodia with acicula-like structures and long capillary chaetae suggests a pelagic lifestyle for this taxon. Our phylogenetic analyses recover Gaoloufangchaeta within the Phyllodocida (Pleistoannelida, Errantia), extending the origin of Errantia back to the early Cambrian. Our data are in line with the hypothesis that Annelida diverged before the Cambrian and indicate both morphological and ecological diversification of annelids in the early Cambrian.